2011
DOI: 10.3382/ps.2010-01037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gas emissions from a Mediterranean broiler farm

Abstract: Gas emissions from broiler production have been the subject of intensive research. However, little experimental information exists for farms under the particular management and environmental conditions of the European Mediterranean area. In this study, ammonia, carbon dioxide, methane, and nitrous oxide concentrations and emissions were measured in a commercial broiler farm located in Spain. Gas concentrations were measured using a photoacoustic gas monitor, whereas the ventilation flow was evaluated by contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 35 publications
14
57
1
9
Order By: Relevance
“…Results are in agreement with previous studies (Seedorf et al, 1998;Calvet et al, 2011) who reported that the ventilation rates increased with bird age and ranged between 1.8 and 4.9 m 3 h À1 bird À1 in winter. However, the ventilation rates in broiler house H3 were higher than broiler houses H1 and H2 (Table 1).…”
Section: Environmental Conditionssupporting
confidence: 83%
See 4 more Smart Citations
“…Results are in agreement with previous studies (Seedorf et al, 1998;Calvet et al, 2011) who reported that the ventilation rates increased with bird age and ranged between 1.8 and 4.9 m 3 h À1 bird À1 in winter. However, the ventilation rates in broiler house H3 were higher than broiler houses H1 and H2 (Table 1).…”
Section: Environmental Conditionssupporting
confidence: 83%
“…Results of this study follow the same trend reported for Mediterranean conditions, by Guiziou and B eline (2005) and Calvet et al (2011) who found a great increase in NH 3 emissions on day 28 during winter. Excluding differences between management practices, the higher NH 3 emission rates obtained in the present study to those reported by Calvet et al (2011) could be related with environmental factors and diets such as the high ventilation rate observed in the referred study (4.9 m 3 h À1 bird À1 in Spain against 3.4 m 3 h À1 bird À1 in Portugal).…”
Section: Ammonia Emissionssupporting
confidence: 77%
See 3 more Smart Citations